Approaching a design space for gameful interactions in the context of piloted driving - Krome, S.; Walz, Steffen; Holopainen, J. (2014)
In this paper, we portray ongoing work aiming to define a design space for enjoyable, playful interactions in the context of a piloted driving situation. Towards this purpose, we identify constraints in the general context of piloted driving, the car's interior and controls as well as the car manufacturer's safety recommendations. Furthermore, we align the identified constraints with proposed stresslessness-strategies for rear-seat passengers in order to anticipate conflicts and choices in the design of gameful interactions for an enjoyable and stress-less piloted driving experience.